Revised Code of Ordinances of the City of Mckinney. Revised Page 40, Image 41 (1899) - (:unkn) unknown (General Publisher, 1899)
That it shall be unlawful for any person, firm or corporation to have or keep stored within the limits of the city of McKinney, at any one time, more than four kegs either of blasting powder or gun powder nor a greater amount of any other high explosive than is reasonably necessary for one day’s business and none of the same shall be kept within the corporate limits of the city of McKinney for wholesale purposes at all.
--
Keywords: GUN POWDER STORAGE